Utilization of a Combination of Papaya (Carica papaya L.) Seed Oil and Virgin Coconut Oil (VCO) in Pomade Formulation and Its Effectiveness Test - Vivi Eulis Diana; Hafizhatul Abadi; Ilmi Ilmi; Akbar Maulana Wahid Hamdani (International Journal of Multidisciplinary Sciences and Arts, 2026)
Pomade is a hair oil made from oily or wax-based ingredients and is applied for hairstyling. The use of pomade is intended to make the hair appear smoother, shinier, and more moisturized. Pomade has been proven to provide longer-lasting hairstyling effects compared to most other hair care products. Papaya seeds (Carica papaya L.) are known to contain chemical compounds such as flavonoids, phenols, alkaloids, terpenoids, and saponins, which are beneficial for promoting hair growth. The enzyme carpain, found in the alkaloid group, is believed to help maintain hair pigment. Meanwhile, virgin coconut oil (VCO) has long been traditionally used to nourish hair. Virgin coconut oil (VCO) contains high amounts of vitamin E, vitamin K, lauric acid, and iron, which serve as essential nutrients and vitamins for moisturizing the hair. This study was conducted experimentally by formulating and testing the stability of pomade preparations using papaya seed oil and VCO at concentrations of 5%, 7.5%, and 10%, followed by evaluation. The evaluation of the formulation included organoleptic tests, homogeneity tests, irritation tests, hedonic (preference) tests, pH tests, spreadability tests, resistance tests, rinsing tests, and stability tests. The results showed that the pomade formulation met the quality and stability evaluation requirements. It had a semi-solid texture, a green tea scent, and different colors for each formulation: F0 was ivory white, F1 (5%) was cream-colored, F2 (7.5%) was cream-colored, and F3 (10%) was yellowish-white. The most preferred formulation was F2 with a 7.5% concentration. All formulations were homogeneous and did not cause skin irritation. They had a pH range of 5.3–6.5, a spreadability range of 4.3–6.5 cm, and demonstrated stable consistency without significant changes. In conclusion, the formulation of pomade using a combination of papaya seed oil (Carica papaya L.) and virgin coconut oil (VCO) can be developed as a pomade that provides a shiny and moisturized hair appearance while preserving hair pigment for long-term use. The concentrations of 5%, 7.5%, and 10% remained stable during the stability tests.